TI_GERICHTE 52.2012.126 vom 19. August 2013 , Tassa per il servizio di raccolta dei rifiuti - principio di equivalenza - TI Tribunale d'appello (2013)
Tassa per il servizio di raccolta dei rifiuti - principio di equivalenza